THE RELATIONSHIP BETWEEN CLASSMATES INTERACTION, MATHEMATICS LEARNING MOTIVATION, AND NUMERICAL ABILITY WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII - Ratih Ika Saputri; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The lack of classmates interaction, lack of motivation to learn mathematics, and low numerical ability in SMP Muhammadiyah 9 Yogyakarta were supposed to influence students' mathematics learning. This research aims to know if there is a positive and significant relationship between classmate's interaction, mathematics learning motivation, and numerical ability with mathematics learning outcomes in student class VIII of even semester at SMP Muhammadiyah 9 Yogyakarta academic year 2016/2017. This study population is all eighth-grade students of SMP Muhammadiyah 9 Yogyakarta academic year 2016/2017, which consists of 5 classes with a total of 160 students. Sampling using a random sampling technique to obtained class VIIIC as a sample of a total of 34 students. Data collection instruments using questionnaires technique and test. Test instrument using validity, different test test, and reliability test. Analysis prerequisite test including normality test, linearity test, and independent test. Data analysis for hypothesis testing using simple correlation analysis and multiple regression analysis. The results showed that itive and significant relationships between classmates' interaction, mathematics learning motivation, and numerical ability with mathematics learning outcomes. The significant level of 5%, and  it shows that Fhitung = 20,5505 and Ftabel= 2,9223 so Fhitung > Ftabel, with multiple correlation coefficient of 0,8279 and the regression equation  The result of determination coefficient of 0,6855 and relative contribution  = 13,8625%,  = 8,8713%,  = 77,2662% and effective contribution  = 9,3250%,  = 5,9675%,  = 51,9749% .